the Efficacy And Safety of Tranexamic Acid in Reducing Blood Loss and Transfusion Requirements During Percutaneous Nephrolithotomy - Abedi, Amir reza; Nikmaram, Raziyeh (Archives of Men's Health, 2025)
Introduction: This study examines TXA as a fibrinolysis inhibitor and blood clot stabilizer to evaluate its effectiveness in improving patient outcomes, reducing blood transfusion rate, and the potential to shorten the surgery duration and hospital stay. Materials and Methods: In this prospective case-control study, 200 patients with kidney stones candidates for Percutaneous nephrolithotomy (PCNL) surgery referred to Tehran's Shohada Tajrish Hospital were selected. In this regard, 100 of them, who received tranexamic acid during the surgery, were allocated to the case group, and the other 100 who did not receive it were assigned to the control group. Statistical tests were used to compare the data between the two groups. Results: The results revealed that 200 patients with kidney stones, with a mean age of 43.38, including 126 males and 46 females, were included in the study. The frequency distribution of demographic data and clinical findings between the two case and control groups was similar (p>0.05). Tranexamic acid administration in the case group compared with the control group reduced the need for blood transfusion by 81 % and reduced the mean surgery period by 21.34 minutes. Additionally, the hemoglobin drop in the case group was significantly lower than that in the control group (P<0.05). The mean change of creatinine did not show a significant difference between the two groups (P>0.05). Conclusion: The results indicate that the prescription of tranexamic acid during PCNL surgery effectively prevents bleeding and hemoglobin drop and reduces the need for blood transfusions and surgery periods without causing specific renal complications.